Keefektivan Beauveria bassiana (Bals.) Vuill. isolat Indigenous pagaralam sumatera selatan pada media beras terhadap larva Plutella xylostella Linn. (Lepidoptera: Yponomeutidae) - Yulia Pudjiastuti; Erfansyah Erfansyah; Siti Herlinda (Jurnal Entomologi Indonesia, 2006)
The objective of study was to investigate the effectiveness of Beauveria bassiana isolate cultured in half-ripe rice media against third-instar larvae of Plutella xylostella. The research used 10 isolates consisted of 4 isolates that were originnally collected from Pagaralam i.e. PD1 (isolated from P. xylostella cadaver), PD2, PD8, PD9B (from Crysodeixis chalcites cadaver), and 6 isolates from other areas as comparison, i.e. CCW3 (from Crysodeixis chalcites cadaver), BBL (from Hypothenemus hampei cadaver), CH (from Conomorpha cramerella cadaver), CPJW (from H. hampei cadavi), WC (from Nilaparvata lugens cadaver), and WSJT (from Leptocorixa acuta cadaver). The parameters that were measured were mortality of larvae, time of death and behaviour of larvae after application. Result of the test showed that B. bassiana isolated from L. acuta (WSJT isolate) caused the highest mortality i.e. 73.34 %, with the highest spore density 5.6x107 spore ml-1 (in half-rice media) and 3.0x107 spore ml-1 (GYA media). The lowest LT50 was 19.27 hours, and was obtained from the application of PD9B. After application of B. bassiana, the behaviour of larvae was slightly change from a healthy one to less in consuming of food and then die.